From ITABs to jobs and skills councils : a contribution to the history of Sector Skills Councils in Australia - Smith, Erica [Verfasser] (My University, 2025)
“This paper throws light on the history of skills councils in Australia from their formal introduction in the 1990s to the present day. Skills councils are important elements of the vocational education and training system, providing two key, and linked, inputs into the vocational education and training (VET) system: they develop the competency standards underpinning the qualifications delivered in VET (Training Packages), and they provide information about industry needs for VET training. They are highly political, as stakeholder groups vie for control of the system; hence during the past thirty years there have been several reorganisations of the system. There has been little research on the topic. The paper describes the four main iterations of the skills council systems over time, using key documents, some no longer available publicly, as well as the author’s own experience in and with the system, and her own research, some unpublished, into the topic. To illustrate the political nature of the system, a case study is provided of the interventions over time by one of the three major economy-wide employer peak bodies. The paper ends with suggestions for further research, and an Appendix documents the major reports of the 2000s and 2010s, including brief summaries, to assist future researchers.” (author’s abstract; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S System beruflicher Bildung; 370; Berufsbildung; Berufsbildungspolitik; Berufsbildungssystem; Kompetenzstandards; Historische Entwicklung; Australien